2001
DOI: 10.1046/j.1464-5491.2001.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐urban differences in the prevalence of the metabolic syndrome in southern India – the Chennai Urban Population Study (CUPS No. 4)

Abstract: Significant differences exist in the prevalence of various components of the metabolic syndrome even within an urban environment and this appears to be influenced by socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(161 citation statements)
references
References 21 publications
11
134
2
4
Order By: Relevance
“…However, there are inter-state differences in energy intake (21) . An earlier study from the Centre (CUPS) (22) conducted in 1997 had shown energy intake of 7456 kJ/d (1782 kcal/d; measured by FFQ), while in the present study, an intake of 10 393 kJ/d (2484 kcal/d) was observed among the present Chennai urban participants, predominantly leading a sedentary lifestyle (75 % of the participants were physically inactive) (20) . Although the energy intake seems to be higher in the present study, methodological constraints and differences in sampling frames limit further interpretation of this finding.…”
Section: Discussioncontrasting
confidence: 56%
“…However, there are inter-state differences in energy intake (21) . An earlier study from the Centre (CUPS) (22) conducted in 1997 had shown energy intake of 7456 kJ/d (1782 kcal/d; measured by FFQ), while in the present study, an intake of 10 393 kJ/d (2484 kcal/d) was observed among the present Chennai urban participants, predominantly leading a sedentary lifestyle (75 % of the participants were physically inactive) (20) . Although the energy intake seems to be higher in the present study, methodological constraints and differences in sampling frames limit further interpretation of this finding.…”
Section: Discussioncontrasting
confidence: 56%
“…[ There was an increase in prevalence of diabetes in Indian urban population due to life style changes which pertained to changes in socioeconomic status [14]. Several studies from the world and India have also tried to find out prevalence of different complications of DM.…”
Section: Resultsmentioning
confidence: 99%
“…Occupation-based physical activity might be related to socioeconomic status, with the moderate-heavy category representing poorer skilled and unskilled laborers, and it is known that BMI can be associated with socio-economic status. 29 Among women, occupation-related physical activity was judged to be inappropriate for two reasons. First, it is unlikely in the Palestinian context to find women involved in occupations involving heavy physical activity.…”
Section: Discussionmentioning
confidence: 99%